أسلوب السياسة الاستعمارية الدموي في احتلال الغرب الجزائري مجزرة أولاد سيدي منصور بتيارت 1864م أنموذجا - صحراوي, الدكتور: كمال، (Sciences de l'Homme et de la Société, 2015)
خلال عمليات التوسع الاستعماري الفرنسي باتجاه الجنوب الغربي الجزائري اصطدمت القوات الفرنسية بمقاومة شديدة عطلت مشروعها زمنًا طويلاً، ومنها مقاومة أولاد سيدي الشيخ التي اندرجت ضمنها مقاومة أولاد سيدي منصور بتيارت، حيث رفضوا ترك أراضيهم وساهموا في مقتل ثلاث فرنسيين بغصني، ولذلك قررت فرنسا الانتقام منهم فهاجمتهم على يد الجنرال مارتينو في سبتمبر 1864 وقتلت منهم (500) فارس شديد حسب روايات الفرنسيين وإحصاءاتهم، ورغم ذلك ظل النسيان يكتنف هذه القضية فقررنا البحث فيها وحصلنا على مجموعة من الوثائق الأرشيفية التي تميط اللثام عنها لعلّ الباحثين يهتمون بها.     Abstract:   During the extending operations of the French colonization towards the Algerian south-west the French forces confronted a hard resistance that stopped their project for a long time, and one of them was the resistance of “ oulad sidi Cheikh ” that included “ oulad sidi Mansor ” resistance in Tiaret, where they refused to leave their lands and contributed in killing three French at Ghosni, therefor General Martineau decided to attack them in September 1864 and killed 500 tough knights according to the French reports and statistics, even so this incident  stays forgotten so we decided to look in it and we’ve got some archive  documents that can encourage researchers to seek its truth.